COMPARING A NEUROPATHOLOGICAL INDEX WITH TRADITIONAL PATHOLOGY IN PREDICTING ALZHEIMER'S DEMENTIA. (11th November 2018) - Wallace, L; Theou, O; Godin, J; Andrew, M; Rockwood, K
Abstract: Background: The hallmark neuropathological features of Alzheimer's disease (AD) don't correlate well with clinical dementia, suggesting cognitive impairment may be multifactorial in older adults with AD. We aimed to assess whether an index of diverse neuropathological features was more strongly associated with Alzheimer's-type dementia than traditional AD neuropathological hallmarks. Methods: This was a cross-sectional analysis of data from the Rush Memory and Aging Project. We constructed a neuropathology index (NPI) using the deficit accumulation approach, as the mean of 10 variables coded between 0 (no pathology) and 1 (severe pathology): percentage of amyloidβ, neurofibrillary tangle density, presence of Lewy bodies, hippocampal sclerosis, cerebral infarcts, cerebral amyloid angiopathy, arteriolosclerosis, atherosclerosis, and TDP-43. A traditional pathology score included plaques (diffuse/neuritic) and tangles. A 41-item frailty index of clinical health data was also calculated for each individual. Cognitive status was determined as AD or no dementia by clinical consensus (all other forms of dementia were excluded). Results: The mean age of 645 included participants was 89.7 ± 6.2 years, 68% female. The NPI ranged from 0–0.87, mean 0.36 ± 0.16. In a logistic regression model controlling for age, sex, and frailty, both NPI and traditional pathology were significantly associated with dementia diagnosis (p<0.001). The NPI outperformed the traditional pathology measure in its ability to classify dementia status (C-statistic 0.80, 95% CI 0.77–0.85 vs. 0.74, 0.70–0.78). Conclusion: An NPI captures information over and above traditional hallmark pathological measures of AD and may help characterize the multifactorial etiologic pathway of dementia in AD.